Attempted suicide: Mode and its distribution characteristics among soldiers and their family - Rawal, Namrata; Shrestha, D B; Katuwal, N; Pathak, N (Journal of Kathmandu Medical College, 2018)
Background: Suicide and Parasuicide are the serious public health problem, which is higher in females, younger people and among unemployed males. Parasuicide being common include mental disorders such as mood disorder, personality disorders, and substance abuse. Para-suicides among military personnels and their families have not been studied yet in Nepal. This study is carried out to understand the demography of parasuicide and its mode. Methodology: This is a hospital record based study including data of last fi ve years (2011-2016 AD) where individuals with history of parasucide were assessed after they were referred to the neuropsychiatry department of military hospital. Their personal detail records and mode of parasuicide were retrieved using simple data retrieval sheet and entered and analysed after approval from local institutional review committee. Results: Among 65 cases attempting suicide, 52.3% were males and 47.7% were females. Median age of individuals attempting suicide was 29 years. Most of the cases (32, 49.2%) attempted suicide were family member of the soldiers then followed by serving and retired soldiers. Among the suicide attempters, organo-phosphorous (OP) poisoning was the commonest mode of suicide attempt (25, 43.1%), followed by drug overdose/ hanging each 11 (16.9%) cases. Conclusion: The study showed that among the soldiers and their family, the commonest mode of parasuicide is OPpoisoning and seen in young males. Journal of Kathmandu Medical College Vol. 7, No. 2, Issue 24, Apr.-Jun., 2018, page: 47-49